Galectin-3 expression in human papillary thyroid carcinoma - Phannee Sawangareetrakul (2018)
Previous studies have suggested that galectin-3 expression was markedly elevated in papillary thyroid carcinoma compared to other thyroid diseases. In order to better understand this protein, galectin-3 from papillary thyroid carcinoma was partially purified by affinity chromatography on lactose-agarose. Proteins eluted from the column were separated by SDS-PAGE, and galectin-3 was detected with antibodies against the N-terminus and C-terminus of galectin-3. Some protein bands from the lactose binding fraction were also selected for identification by liquid chromatography/mass spectrometry/mass spectrometry (LC/MS/MS). Seven protein bands, with molecular weights ranging from 16 kDa to 31 kDa, were identified as galectin-3. The antibody raised against the C-terminus of galectin-3 gave a strong band for one of the bands detected by the N-terminal antibody and weak bands for the other three. One additional dark immunoreactive band with an approximate molecular weight of 20 kDa, was also detected by the C-terminal galectin-3 antibody. To determine the structural differences of each protein band N-terminal amino acid sequencing of the seven protein bands was conducted. The three upper bands were N-terminally blocked, while the other bands had N-terminal amino acid sequences starting at positions Gly35, Gly65 (2 bands) and Ala100, respectively. Further studies are necessary to determine whether these are due to nonspecific proteolysis or post-translation modification.